First record of the Atlantic blue crab Callinectes sapidus (Crustacea: Brachyura: Portunidae) in the Segura River mouth (Spain, southwestern Mediterranean Sea) - González-Wangüemert, Mercedes (2017)
A single male individual of Callinectes sapidus (Crustacea, Decapoda, Portunidae) was collected on 6 December 2014 in the Segura River mouth in southeastern Spain. Information on collection site, DNA barcoding, and its present distribution and dispersal strategies are provided.